Implementation of Data Warehouse and Star Schema for Optimizing Property Business Decision Making - Willsen Wijaya; Jansen Wiratama; Santo Fernandi Wijaya (Universitas Islam Raden Rahmat, Malang, 2024)
The property industry is a sector that faces intense competition, so innovation is needed to plan business strategies. PT Wijaya Karya Realty faces several problems, such as determining strategic locations for its property products, such as houses or shophouses, and comparing the price of company houses with the market price of homes in specific locations. To answer these needs, it is necessary to implement a data warehouse and Extract, Transform, Load (ETL). In this research, Pentaho Data Integration (PDI) is used as a tool for managing and cleaning data that can be used as analysis material to assist in data-based decision-making. Apart from that, Mondrian can be used through the workbench scheme to improve data analysis effectively. Designing a star schema that includes a dimensional table and fact table can help optimize the analysis process better. The implementation of a data warehouse allows companies to make in-depth decisions based on critical variables. The research results show that the implementation of Star Schema can provide information for companies in decision-making and business strategy planning in the property sector.